Evaluation of Rumensin® in late season, salt-limited, protein supplements fed to grazing steers and heifers - L.R. Corah; F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1986)
Even though an average daily Rumensin® consumption of over 100 mg per was achieved in all three trials, it did not significantly improve daily gains of steers or heifers grazing late-season native range. Late-season protein supplementation improved average daily gain by over .2 lb per head.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Rumensin®; Protein; Salt